2012
DOI: 10.1186/1475-2891-11-47
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Korean red ginseng on lymphocyte DNA damage, antioxidant enzyme activity, and LDL oxidation in healthy participants: a randomized, double-blind, placebo-controlled trial

Abstract: BackgroundThe reported health benefits of Korean red ginseng (KRG) include antioxidant, antitumor, antimutagenic, and immunomodulatory activities; however, the effects on oxidative stress have not yet been evaluated. Therefore, we assessed the effect of KRG on antioxidant enzymes and oxidative stress markers in humans.MethodsWe conducted a randomized, double-blind, placebo-controlled study with three groups, including placebo, low-dose (3 g/day), and high-dose (6 g/day), which were randomly assigned to healthy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
48
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 22 publications
2
48
0
1
Order By: Relevance
“…1,2 Recent studies have reported various effects of red ginseng, including antioxidant, antitumor, antimutagenic, antidiabetic, and immunomodulatory activities. 3,4 Accumulating evidence suggests that the major pharmacologically active ingredients are ginsenosides, which have a four-ring, steroid-like structure with attached sugar moieties.…”
Section: Introduction Rmentioning
confidence: 99%
“…1,2 Recent studies have reported various effects of red ginseng, including antioxidant, antitumor, antimutagenic, antidiabetic, and immunomodulatory activities. 3,4 Accumulating evidence suggests that the major pharmacologically active ingredients are ginsenosides, which have a four-ring, steroid-like structure with attached sugar moieties.…”
Section: Introduction Rmentioning
confidence: 99%
“…There was a decrease in cancer risk in chronic atrophic gastritis patients with 3 years of intervention with the Korean red ginseng extract in an 8-year follow-up study [ 22 ].Korean red ginseng powder and the 20% ethanol ginseng extract showed antioxidative effects in postmenopausal females or healthy subjects [ 23 , 24 , 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…Since ginseng is identified as a natural antioxidant in lab and animal researches (54), several studies examined the antioxidant effects of different types of ginseng on human or animals. However, based on the present systematic search, all the studies compared ginseng with placebo but none of them compared ginseng with other antioxidants (55)(56)(57)(58). To the best knowledge of the researchers, most of the trials were conducted on men's sexual and erectile dysfunction (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%